220k views
0 votes
Solve for x: (1 point)

-9/8, * x - 7=-25

User Mr Bean
by
4.8k points

2 Answers

5 votes

Answer: x=16

Step-by-step explanation: Rearrange the equation by subtracting what is to the right of the equal sign from both sides of the equation :

-9/8*x-7-(-25)=0

simplify 9/8

((0 - (9/8 • x)) - 7) - -25 = 0

Subtracting a whole from a fraction

Rewrite the whole as a fraction using 8 as the denominator

7 = 7/1 = 7*8/8

Equivalent fraction : The fraction thus generated looks different but has the same value as the whole

Common denominator : The equivalent fraction and the other fraction involved in the calculation share the same denominator

-9x - 56 = -1 • (9x + 56)

Adding up the two equivalent fractions

(-9x-56) - (-25 • 8)/8 144 - 9x/8

144 - 9x = -9 • (x - 16)

When a fraction equals zero ...

Where a fraction equals zero, its numerator, the part which is above the fraction line, must equal zero.

Now,to get rid of the denominator, multiply both sides of the equation by the denominator.

Here's how:

-9•(x-16)/8 • 8 = 0 • 8

Now, on the left hand side, the 8 cancels out the denominator, while, on the right hand side, zero times anything is still zero.

The equation now takes the shape :

-9 • (x-16) = 0

Solve : x-16 = 0

Add 16 to both sides of the equation :

x = 16

User Julieanne
by
5.5k points
2 votes

Answer: x=16

Step-by-step explanation: Rearrange the equation by subtracting what is to the right of the equal sign from both sides of the equation :

-9/8*x-7-(-25)=0

simplify 9/8

((0 - (9/8 • x)) - 7) - -25 = 0

Subtracting a whole from a fraction

Rewrite the whole as a fraction using 8 as the denominator

7 = 7/1 = 7*8/8

Equivalent fraction : The fraction thus generated looks different but has the same value as the whole

Common denominator : The equivalent fraction and the other fraction involved in the calculation share the same denominator

-9x - 56 = -1 • (9x + 56)

Adding up the two equivalent fractions

(-9x-56) - (-25 • 8)/8 144 - 9x/8

144 - 9x = -9 • (x - 16)

When a fraction equals zero ...

Where a fraction equals zero, its numerator, the part which is above the fraction line, must equal zero.

Now,to get rid of the denominator, multiply both sides of the equation by the denominator.

Here's how:

-9•(x-16)/8 • 8 = 0 • 8

Now, on the left hand side, the 8 cancels out the denominator, while, on the right hand side, zero times anything is still zero.

The equation now takes the shape :

-9 • (x-16) = 0

Solve : x-16 = 0

Add 16 to both sides of the equation :

x = 16

User Smittey
by
4.4k points